The Evolution of Brexit and Its Impact on European Education and Research Programmes - Ciccone, Giuseppe (Border Crossing, 2025)
Brexit has represented a historic transformation in the relationship between the United Kingdom (UK) and the European Union (EU), with significant impacts not only on the political and economic level, but also in the educational and academic spheres. This article explores the effects of Brexit on student mobility and research, analysing in detail the repercussions of the end of the UK's participation in crucial programmes such as Erasmus+ and Horizon Europe. In particular, it examines how the UK, after its withdrawal from Erasmus+, established the Alan Turing Scheme to support the international mobility of British students, albeit with reduced funding compared to the European programme. The impact on UK universities and their opportunities to participate in joint research initiatives is also discussed, highlighting the growing competition for Horizon Europe funds and the increase in bureaucracy following the separation from the European single market. The work concludes with a reflection on the future prospects for the UK and the EU, underlining the need for adaptations to migration, economic and research policies to mitigate the effects of Brexit and foster broader international cooperation. Finally, possible research directions are suggested to better understand the evolution of educational mobility programs, migration policy management and post-Brexit economic competitiveness, with particular attention to the growing role of global alliances such as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP).